Cognitive Behavior Therapy for Generalized Anxiety Disorder: A Case Study of Arrhythmia Patient - Dewinta, Putri; Menaldi, Adhityawarman (Humaniora, 2018)
This research aimed to test the efficacy of Cognitive Behavior Therapy (CBT) and psychoeducation methods to decrease anxiety level in arrhythmia patient. Besides that, it was also to discuss how CBT could reduce anxiety level on a subject who had Generalized Anxiety Disorder (GAD) and also had the medical disease. This research used the qualitative method. The subject in this research was a 22-years-old single female, called S (initials), who came to community health center (Puskesmas) to get help regarding her uncomfortable feelings about her thoughts and concerns. The subject was given a pre-post test using Hamilton Anxiety Rating Scale (HARS) to see the differences in the anxiety level before, during, and after the treatment. Results of the research show that the level of anxiety in the subject is decreased. The categorization score goes from “very severe anxiety” to “moderate anxiety”. The subject also conveys on the last session that she feels less anxious and that she can control her negative thought.